A 5-day course of oral antibiotics followed by faecal transplantation to eradicate carriage of multidrug-resistant Enterobacteriaceae: a randomized clinical trial. (July 2019) - Huttner, B.D.; de Lastours, V.; Wassenberg, M.; Maharshak, N.; Mauris, A.; Galperine, T.; Zanichelli, V.; Kapel, N.; Bellanger, A.; Olearo, F.; Duval, X.; Armand-Lefevre, L.; et al.
Abstract: Objectives: Intestinal carriage with extended spectrum β-lactamase Enterobacteriaceae (ESBL-E) and carbapenemase-producing Enterobacteriaceae (CPE) can persist for months. We aimed to evaluate whether oral antibiotics followed by faecal microbiota transplantation (FMT) can eradicate intestinal carriage with ESBL-E/CPE. Methods: Randomized, open-label, superiority trial in four tertiary-care centres (Geneva (G), Paris (P), Utrecht (U), Tel Aviv (T)). Non-immunocompromised adult patients were randomized 1: 1 to either no intervention (control) or a 5-day course of oral antibiotics (colistin sulphate 2 × 10 6 IU 4×/day; neomycin sulphate 500 mg 4×/day) followed by frozen FMT obtained from unrelated healthy donors. The primary outcome was detectable intestinal carriage of ESBL-E/CPE by stool culture 35–48 days after randomization (V4). ClinicalTrials.gov NCT02472600 . The trial was funded by the European Commission (FP7). Results: Thirty-nine patients (G = 14; P = 16; U = 7; T = 2) colonized by ESBL-E ( n  = 36) and/or CPE ( n  = 11) were enrolled between February 2016 and June 2017. In the intention-to-treat analysis 9/22 (41%) patients assigned to the intervention arm were negative for ESBL-E/CPE at V4 (1/22 not receiving the intervention imputed as positive) whereas in the control arm 5/17 (29%) patients were negative (one lost to follow up imputed as negative) resulting in an OR for decolonization success of 1.7 (95% CI 0.4–6.4). Study drugs were well tolerated overall but three patients in the intervention group prematurely stopped the study antibiotics because of diarrhoea (all received FMT). Conclusions: Non-absorbable antibiotics followed by FMT slightly decreased ESBL-E/CPE carriage compared with controls; this difference was not statistically significant, potentially due to early trial termination. Further clinical investigations seem warranted.